Relações filogenéticas em crinocheta (Isopoda, Oniscidea) - Araújo, Joafrâncio Pereira de (2017)
Terrestrial isopods (Crustacea, Oniscidea) constitute the most successful group among the crustaceans that colonized the terrestrial environment. Actually, there are about 3,700 known species. Only three proposals, directly and indirectly, sought to understand the evolutionary patterns within Crinocheta (a monophyletic group of Oniscidea with approximately 2,750 species). The results of these proposals were inconclusive, leading the authors to assume that the phylogenetic relationships presented are weakly supported. It was intended to refine and seek new evolutionary evidence for the phylogenetic relationships in Crinocheta, evaluating the phylogenies already proposed in the literature. All available taxonomic literature was used referring to the taxa of Oniscidea and related subjects, mainly for Crincoheta. Pictorial cards were constructed for comparative analysis of the illustrated structures. From this process it was possible to see some structures that were tried to place within an evolutionary context along with the taxa that hold these characters. Initially it was concluded that there are few groups in Crinocheta that are strongly supported monophyletic units. The families are mostly paraphyletic groups, this being one of the main problems to use this taxonomic level as terminal taxa of the phylogenetic analyzes already published. Therefore, this work is the beginning of a laborious research that intends to propose consistent monophyletic groups for the Crinocheta lineage. Failure to follow the procedures normally used for cladistic analysis is due to the fact that previous attempts have not been very successful in their results.